(untitled) (Bioagro, 2024)
Colombia is one of the largest producers, consumers, and exporters of diploid potatoes. We evaluated the effect of different sources and doses of fertilization on the growth of potato Criolla Colombia and Ocarina. The seed was planted in furrows 0.5 cm deep and 0.30 m x 1.00 m away (33,333 plants·ha-1). Treatments were the combination of variety and fertilizer [15-15-15 (FQA); urea, diamonic phosphate and potassium chloride, after soil analysis (FQ); organic mineral fertilizer (FOM) and the mixture of 50 % of individual fertilizers]. Sampling of three plants per treatment was performed in each phenological phase to determine: phenological development (PD), leaf area (LA), leaf specific weight (LSW), and rates: net assimilation (NAR), relative growth (RGR) and crop growth (CGR). The design was a 2x7 factorial arrangement of random complete blocks with repeated measurements, four replications, and 60 m2 as an experimental unit, with three plants as the effective plot. Fertilization only affected PD and LA, with the highest LA for FQA (115 days after sowing – das). NAR, RGR, and CGR were higher for the Colombia variety. The reduction of NAR and RGR (110 to 115 das) coincided with flowering, and the increase of CGR and LA (115 das) with tuberization. Fertilization only affected PD and LA, regardless of the variety. FQA + FQ favored the greater PD and FQA the greater LA. The Colombia variety was early and stood out on growth.